The Relationship Between Learning Styles and Student Learning Outcomes Through Team Game Tournament Learning Integrated with The P5 - Anik Widiastuti; Eki Yulia Susanti; Diana Ayu Pamungkas; M. Khoiri Nursalim (SOSEARCH : Social Science Educational Research, 2026)
Previous studies have shown that the Teams Games Tournament (TGT) model is effective in enhancing student engagement; however, they have not explicitly examined how this effectiveness is influenced by differences in learning styles within the context of the integration of the Proyek Penguatan Profil Pelajar Pancasila (P5). This gap serves as a critical foundation for the present study. This study aims to analyze the relationship between learning styles and student learning outcomes through a P5-integrated TGT model using a quantitative correlational-comparative design. The research subjects consisted of 64 students at SMPN 2 Depok, categorized into auditory, visual, and kinesthetic learning preferences. The instruments used included a learning style questionnaire, achievement tests, peer assessment observation sheets, and teacher journals to measure the attainment of the Pancasila Student Profile dimensions. Data were analyzed using the Kruskal-Wallis test and Spearman correlation. The results indicate a significant difference in learning outcomes based on students’ learning styles (p = 0.000), with kinesthetic students demonstrating superior performance within the TGT framework compared to auditory and visual students. Furthermore, the Spearman correlation reveals a strong relationship between learning styles and academic achievement (ρ = 0.886, p = 0.000), indicating a very strong association between the two variables. The novelty of this study lies in the integration of learning style analysis, the TGT learning model, and the implementation of P5 within a single measurable empirical framework. Practically, this study recommends the implementation of TGT-based differentiated instruction, such as the use of visual media and structured verbal reinforcement, to ensure that all learning styles are optimally accommodated.